Mandatory Portfolio Disclosure, Stock Liquidity, and Mutual Fund Performance - Agarwal, Vikas (Institutional Knowledge at Singapore Management University, 2013)
This paper studies the impact of mandatory portfolio disclosure of mutual funds on the liquidity of disclosed stocks and on fund performance. We consider a theoretical model of informed trading with different mandatory disclosure frequencies. Using a regulation change in May 2004 that increased the frequency of mandatory disclosure, we find evidence consistent with the model’s predictions. First, stocks with higher fund ownership experience a larger increase in liquidity as compared to other stocks subsequent to the mandatory increase in disclosure frequency, especially for stocks disclosed by more informed funds or subject to greater information asymmetry. Second, better performing funds experience a greater drop in their abnormal performance following the regulation change, particularly when they hold stocks with greater information asymmetry or when they take longer to complete their trades. Taken together, our evidence suggests that mandatory portfolio disclosure improves market quality by increasing stock liquidity but imposes costs on informed investors.